miR-1249-5p regulates the osteogenic differentiation of ADSCs by targeting PDX1 - Yang, Xiao-Mei (J Orthop Surg Res, 2021)
BACKGROUND: Osteoporosis (OP) is an age-related systemic bone disease. MicroRNAs (miRNAs) are involved in the regulation of osteogenic differentiation. The purpose of this study was to explore the role and mechanism of miR-1249-5p for promoting osteogenic differentiation of adipose-derived stem cells (ADSCs). METHODS: GSE74209 dataset was retrieved from NCBI Gene Expression Omnibus (GEO) database and performed bioinformatic analyses. OP tissue and healthy control tissues were obtained and used for RT-PCR analyses. ADSCs were incubated with miR-1249-5p mimic, inhibitor and corresponding negative control (NC), alkaline phosphatase (ALP) staining, and Alizarin Red Staining (ARS) were then performed to assess the role of miR-1249-5p for osteogenesis of ADSCs. Targetscan online website and dual-luciferase reporter assay were performed to verify that the 3′-UTR of PDX1 mRNA is a direct target of miR-1249-5p. RT-PCR and western blot were also performed to identify the mechanism of miR-1249-5p for osteogenesis of ADSCs. RESULTS: A total of 170 differentially expressed miRNAs were selected, among which, 75 miRNAs were downregulated and 95 miRNAs were upregulated. Moreover, miR-1249-5p was decreased in OP patients, while showed a gradual increase with the extension of induction time. miR-1249-5p mimic significantly increased osteogenic differentiation capacity and p-PI3K and p-Akt protein levels. Luciferase activity in ADSCs co-transfected of miR-1249-5p mimic with PDX1-WT reporter plasmids was remarkably decreased, but there was no obvious change in miR-1249-5p mimic with PDX1-MUT reporter plasmids co-transfection group. Overexpression PDX1 could partially reverse the promotion effects of miR-1249-5p on osteogenesis of ADSCs. CONCLUSION: In conclusion, miR-1249-5p promotes osteogenic differentiation of ADSCs by targeting PDX1 through the PI3K/Akt signaling pathway.